Lifestyle and medicine in the Enlightenment
1 online resource
Keywords: The biggest challenges in public health today are often related to attitudes, diet and exercise. In many ways, this marks a return to the state of medicine in the eighteenth century, when ideals of healthy living were a much more central part of the European consciousness than they have become since the advent of modern clinical medicine. Enlightenment advice on healthy lifestyle was often still discussed in terms of the six non-naturals - airs and places, food and drink, exercise, excretion and retention, and sleep and emotions. This volume examines what it meant to live healthily in the Enlightenment in the context of those non-naturals, showing both the profound continuities from Antiquity and the impact of newer conceptions of the body.